Low‐Temperature Thermochronologic Response to Magmatic Reheating: Insights From the Takab Metallogenic District of NW Iran, (Arabia‐Eurasia Collision Zone). (24th January 2023) - Biralvand, Masoud; Ballato, Paolo; Balestrieri, Maria Laura; Mohajjel, Mohammad; Sobel, Edward R.; Dunkl, Istvan; Montegrossi, Giordano; Ghassemi, Mohammad R.; Glodny, Johannes; Strecker, Manfred R.
Abstract: The interpretation of low‐temperature thermochronology (LTT) data in magmatic and metallogenic provinces requires a knowledge of the geothermal field through time. There, the challenge is differentiating rapid cooling following transient perturbations of the geotherms (reheating) from exhumational cooling induced by erosion during tectonic uplift or normal faulting. The Takab Range Complex (NW Iran) is a basement‐cored range of the Arabia‐Eurasia collision zone that experienced voluminous Eocene to Miocene magmatism and mineralization. Our new apatite and zircon (U‐Th‐Sm)/He and apatite fission track data, together with field observations, a dedicated numerical thermal model, and a re‐evaluation of available geochronology data document the occurrence of a complex geological and thermal history including: (a) late Cretaceous‐Paleocene exhumation possibly controlled by regional contractional deformation followed by Eocene deposition; (b) Oligocene to possibly early Miocene (29 to 22–20 Ma) exhumation of basement rocks from 13 to 8 km of depth, most likely through normal faulting during a thermal anomaly that led to migmatization and partial melting; (c) early to late Miocene (∼22–20 or earlier to 11–10 Ma) regional subsidence with deposition of an up to ∼2‐ to 3‐km‐thick Oligo‐Miocene sedimentary sequence in association with the emplacement of shallow intrusions, which led to a partial to total reset of our LTT systems sometime between 18 and 13 Ma; and (e) erosional exhumation after 11–10 Ma with the development of a transpressional system and a master, right‐lateral, strike slip fault (Chahartagh Fault). Our data highlights the impact of magmatic reheating on LTT ages in areas affected by intense magmatism. Key Points: Erosional exhumation and tectonic denudation occurred during the late Cretaceous‐Paleocene and the Oligocene, respectively Widespread resetting of ZHe, Apatite Fission Track, and AHe systems occurred between 18 and 13 Ma through magmatic reheating of shallow intrusions (<10 km) Erosional exhumation after 11–10 Ma from shallow depths (<2–3 km) was caused by transpressional deformation